Behavioural Finance and Stock Investment Decisions - Sapkota, Mohan Prasad (Saptagandaki Journal, 2022)
Market anomalies is the source of inefficient market where investors can generate abnormal return which is the centre point of behaviour finance. Behavioural finance incorporates the human behaviour, cognitive and social aspects, emotions, moods and psychology of the individual investors that might create investment mistakes. This study focuses on exploring the influence of behavioural finance on stock investment decision of the master level students in Chitwan district due to poor literature available in this field. This study is based on quantitative approach of research and utilizes analytical research design. The sample of the study is 284 students with usable response rate of 60.21 percent. This study utilizes reliability analysis, descriptive statistics and multiple regression analysis. Evidence indicates that herding, loss aversion, overconfidence and risk propensity has significant positive influence on stock investment decisions among investors. Finally, this study concluded that behavioural finance plays the key role while making stock investment decision of the students. In investment decision, investors should properly understand financial behaviour biases that facilitates investors while making superior investment decisions as well as risk propensity will make investors aware of fears, nervous and uncertainty toward risks which might occurs while making stock investment decisions.